Undersökning av möjligt nyttjande av outnyttjad kapacitet genom energieffektiviserande våningspåbyggnad på befintliga murade stommar - Ekeroth,Rasmus; Ekman,Isak (TVBK-5000, 2023)
As a part of the Green Deal within the EU, as of the start of 2023, new demands have been put in place in an energy taxonomy on companies providing financial services, a category in which real estate companies are included. The investments of these companies are now to be classified as sustainable or not sustainable. Another part of the shift towards sustainability within the EU is that the existing real estate stock is expected to get tougher energy efficiency demands. As a solution to the demands the possibility of investing in energy effective vertical extension and therefore also making sustainable investments in accordance with the taxonomy is investigated. The possibility of vertical extension on the Swedish “smalhus” constructed during the 1930s to the 1950s is largely unknown. The residential building type was produced at large scale of around 55 000 apartments in the building type only in greater Stockholm. Through systematic application of the current EU-standard for assessment of existing structures the possibility of vertical extension of upwards of three stories at a typical “smalhus” with a brick masonry load bearing structure was investigated through a case study. In addition to the case study, a literature study of vertical extension principles, material properties and older Swedish building codes was carried out. Through translation of the at the time of construction active building norms the verification methods of today were made applicable. The results show great possibilities for vertical extension in the brick masonry structures of the time, but that a series of challenges must be faced in verification. It was shown that the foundation of the structure did not meet the verification demands after updating the loads to current day standards. Further, horizontal loading was shown to be critical for the case study structure. Regarding new demands of building robustness, the case study structure was not verifiable. The shift between norms at the time of construction and present day was complicated. The load combinations of today result in higher loading. Structural engineers must work carefully with the “smalhus” building type constructed with low strength mortars since these are challenging to verify regarding horizontal loading. Methods of material testing as well as construction material compositions differ from current day standards. In evaluating the norm for assessment of existing structures it is shown to be imperative in iterating and revising the structural engineers’ models of verification. The reliability in used data such as material properties and building geometries is of great importance and should be completed with testing.